دور الصوفية والكونفوشيوسية الجديدة في ترسيخ الإسلام في الصين: The Role of Sufism and Neo-Confucianism in Promoting Islamic Identity in China - dan 赵丹, Zhao; Binti Ahmad, Masitoh (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2024)
ملخص البحث الصوفية والكونفوشيوسية الجديدة تمثلان تيارين فكريين وفلسفيين بارزين في تاريخ الصين، وقد لعبا دورا هاما في نشر الإسلام في البلاد من خلال التفاعل الثقافي والفكري. فالصوفية، ببعدها الروحي العميق، قدمت الإسلام بطريقة تتماشى مع القيم الروحية التقليدية، بينما قدمت الكونفوشيوسية الجديدة، ببعدها الفلسفي والأخلاقي، إطارا ثقافيا وفكريا ساعد في تقبل الإسلام بين السكان المحليين. غير أن الانطباعات العامة لدى الناس أن الصين بلد وثني أو لاديني، وقليل ما يعرفون أن الإسلام في الصين راسخ وقديم، فضلا عن الأدوار التي لعبتها كل من الصوفية والكونفوشيوسية حيث قام من خلال هذا تيارات مثل "هان كتاب". يهدف هذا البحث إلى دراسة التفاعلات بين الصوفية ووالكونفوشيوسية وبين الفلسفة الصينية التقليدية في ترسيخ الهوية الإسلامية في الصين ودورهما في جعل الإسلام أكثر قبولا في الصين. يعتمد هذا البحث على المنهج الوصفي التحليلي. وتوصل إلى أن الصوفية والكونفوشيوسية ساهمتا في خلق بيئة من التسامح والتعايش بين المسلمين وغير المسلمين، مما سهل عملية نشر الإسلام وهويته في الصين. ABSTRACT Sufism and Neo-Confucianism are two prominent intellectual and philosophical movements in Chinese history, and they have played an important role in spreading Islam in the country through cultural and intellectual interaction. Sufism, with its profound spiritual dimension, presented Islam in a way that was consistent with traditional spiritual values, while Neo-Confucianism, with its philosophical and moral dimension, provided a cultural and intellectual framework that helped the Chinese indigine accept Islam. The general impression was that China was a pagan or irreligious country, and little did people know that Islam in China was well-established and old, talkless of the roles played by both Sufism and Confucianism, through thses movements such as the “Han Kitab” emerged. This research aims to study the intellectual interactions between Islamic Sufism and traditional Chinese philosophy in consolidating the Islamic identity in China and their role in making Islam more acceptable in China. This research adopts a descriptive and analytical approach to study the role of Sufism and Neo-Confucianism in consolidating Islam in China. The research concluded that Sufism and Confucianism contributed to creating an environment for tolerance and coexistence between Muslims and non-Muslims, which facilitated the process of spreading Islam and its identity in China.